A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru - Venegas, Pablo J.; Echevarría, Lourdes Y.; García-Burneo, Karla; Koch, Claudia (Zootaxa, 2016)
We describe a new species of Stenocercus from the montane forest of the right margin of the Marañón river in the northern portion of the Central Andes in northern Peru (Amazonas and La Libertad departments), at elevations ranging from 2300 to 3035 m. Stenocercus omari sp. nov. differs from other Stenocercus species, with the exception of S. amydrorhytus, S. chrysopygus, S. cupreus, S. johaberfellneri, S. latebrosus, S. melanopygus, S. modestus, S. ornatissimus, S. orientalis, and S. stigmosus, by having granular scales on the posterior surfaces of thighs, a conspicuous antehumeral fold and by lacking a vertebral crest. However, Stenocercus omari sp. nov. is easily distinguished from the aforementioned species, except S. orientalis, by the presence of prominently keeled dorsal head scales. The new species differs from S. orientalis by lacking a prominent oblique neck fold and by having a distinct deep postfemoral mite pocket.